2017
DOI: 10.1177/2324709617728750
|View full text |Cite
|
Sign up to set email alerts
|

Median Arcuate Ligament Syndrome: It Is Not Always Gastritis

Abstract: Median arcuate ligament syndrome is a rare disorder that is clinically characterized by the triad of postprandial abdominal pain, weight loss, and often an abdominal bruit due to compression of the celiac artery by the median arcuate ligament. Given the nonspecific symptoms, this is a rare and difficult diagnosis to obtain. We present a patient with nonspecific abdominal pain in whom etiology was ultimately determined to be median arcuate ligament syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 7 publications
0
33
1
1
Order By: Relevance
“…An abdominal bruit is reported to be present in many| patients with MAL syndrome. Sunkara T et al 9 and Watari T et al 10 and many other authors have reported presence of bruit in patients with MAL syndrome whereas bruit was absent in patients reported by Kuruvilla A et al 11 The diagnosis of MAL can be suspected in young patients particularly females presenting with post-prandial abdominal pain, vomiting and weight loss. Abdominal Bruit may or may not be present.…”
Section: Discussionmentioning
confidence: 94%
“…An abdominal bruit is reported to be present in many| patients with MAL syndrome. Sunkara T et al 9 and Watari T et al 10 and many other authors have reported presence of bruit in patients with MAL syndrome whereas bruit was absent in patients reported by Kuruvilla A et al 11 The diagnosis of MAL can be suspected in young patients particularly females presenting with post-prandial abdominal pain, vomiting and weight loss. Abdominal Bruit may or may not be present.…”
Section: Discussionmentioning
confidence: 94%
“…Results following surgery may be varied. Many patients (up to 60%-70%) have successful resolution of symptoms however since post-operative pain may persist following intervention, pain may not resolve for several months following surgery [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…The ligament passes above the origin of the celiac artery and is a direct continuation of the posterior diaphragm that wraps over the aorta [1]. In 10% to 24% of the population, an unusually low-lying MAL passes anterior to the celiac artery causing some degree of stenosis triggering abdominal symptoms [1,2,6]. Celiac trunk is most prone to constriction by MAL when the distance between the celiac trunk root and the diaphragmatic crura is short, i.e, an abnormally low-lying diaphragmatic MAL [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Median arcuate ligament syndrome (MALS), also known as coeliac axis compression syndrome or Dunbar syndrome, is a rare disorder resulting from the external compression of the celiac trunk by the MAL [1,4]. MALS is characterized by the triad of postprandial abdominal pain, weight loss, and often an abdominal bruit produced due to celiac artery compression by MAL [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation